Providers’ Initial Trust on an Organization-Sponsored Sharing Platform: The Framing of Coworker Collaborative Consumption - Bhappu, Anita D.; Blomqvist, Kirsimarja; Andreeva, Tatiana; Zappa, Paola; Yeo, M. Lisa; Lempiälä, Tea (Frontiers in Psychology, 2020)
Organization-sponsored sharing platforms extend the sharing economy to workplaces by connecting employees in a private online community where they can socially exchange goods and services with coworkers. Employees share costs but do not earn income during this collaborative consumption. Furthermore, employers pay for their employees to have access to the platform technology and any related transaction fees. Trust is a crucial antecedent for engagement on sharing platforms because it helps mitigate risks during collaborative consumption. However, the literature on trust in the sharing economy has focused almost exclusively on platforms that broker peer-to-peer rentals transactions rather than social exchanges. There is also a lack of research about providers’ perspectives. We address these gaps by investigating the nature of trust among employees who initially provide goods and services on an organization-sponsored sharing platform. We also explore how these employees’ initial trust influences their collaborative consumption with coworkers. Through abductive analysis of 22 interviews with 15 providers on an organization-sponsored sharing platform, we shed light on how employees initially develop trust when providing goods and services to coworkers. By integrating prior research on initial trust among employees and cognitive framing with in-depth qualitative insights, we develop a conceptual model depicting how identity, interaction and issue frames shape these providers’ beliefs about coworker trustworthiness and intended sharing strategy. In particular, our empirical findings reveal that employees’ social categorization, illusions of control and engagement motive framed their initial trust and enactment of collaborative consumption as citizens in a community or consumers in a marketplace.